Regulating Acidosis and Relieving Hypoxia by Platelet Membrane-Coated Nanoparticle for Enhancing Tumor Chemotherapy - Luo, Xingyu; Cao, Jian; Yu, Jianming; Dai, Dongqing; Jiang, Wei; Feng, Yahui; Hu, Yong (Frontiers in Bioengineering and Biotechnology, 2022)
Acidosis and hypoxia of tumor remain a great challenge for cancer therapy. Herein, we developed Hb-LOX-DOX-ZIF8@platelet membrane nanoparticles (H-L-D-Z@PM NPs) to address this problem. Lactate oxidase (LOX) could deplete intratumoral lactate adequately and amplify oxidative stress efficiently. In the meantime, hemoglobin (Hb) was intended to deliver oxygen, relieve hypoxia, and boost the catalytic activity of LOX. The coated PM bestowed active tumor-targeting ability and good biocompatibility to these nanoparticles. Moreover, the encapsulation of zeolitic imidazolate framework-8 (ZIF8) offered the acid response capacity to nanoparticles. With the synergism of chemotherapy drug doxorubicin (DOX), these H-L-D-Z@PM NPs appeared to have excellent antitumor competence. Collectively, this study offered a new strategy for enhancing tumor chemotherapy by regulating acidosis and relieving hypoxia.